2012
DOI: 10.1017/s0017089512000080
|View full text |Cite
|
Sign up to set email alerts
|

Consistency Conditions for Dimer Models

Abstract: Abstract. Dimer models are a combinatorial tool to describe certain algebras that appear as noncommutative crepant resolutions of toric Gorenstein singularities. Unfortunately, not every dimer model gives rise to a noncommutative crepant resolution. Several notions of consistency have been introduced to deal with this problem. In this paper, we study the major different notions in detail and show that for dimer models on a torus, they are all equivalent.2010 Mathematics Subject Classification. 14M25, 14A22, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 21 publications
0
94
0
Order By: Relevance
“…The analogue problem for brane tilings and, more generally, bipartite graphs on Riemann surfaces has been extensively studied (see e.g. [35][36][37][38][39][40][41][42] and references therein). In this section we take the first steps on this issue for brane brick models, proposing natural generalizations of the brane tiling case.…”
Section: Consistency and Reductionmentioning
confidence: 99%
“…The analogue problem for brane tilings and, more generally, bipartite graphs on Riemann surfaces has been extensively studied (see e.g. [35][36][37][38][39][40][41][42] and references therein). In this section we take the first steps on this issue for brane brick models, proposing natural generalizations of the brane tiling case.…”
Section: Consistency and Reductionmentioning
confidence: 99%
“…To characterize such dimer models we introduce a notion of consistency. Several different notions are available in the literature [22,12,13,36,25,11] but we will restrict to one: zigzag consistency. Fix a dimer model Q and its universal coverQ u , which is again a dimer.…”
Section: 4mentioning
confidence: 99%
“…In [13] Davison proved that the cancellation property alone implies the Calabi-Yau property and that this second technical condition follows from the cancellation property. In [11] it is shown that zigzag consistency implies the cancellation property. Similar results are also obtained by Ishii and Ueda in [24] and [25].…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations